Desktop Analysis and Qualitative Investigation of Programmes and Initiatives for the Prevention of and Response to Gender Based Violence at South African Universities with Medical Campuses - Hewett, M.; Butler-Kruger, L.; Foflonker, K.; Edge, J.; Botha, M. H.; Seedat, S. (South African Journal of Higher Education, 2023)
Gender-based violence (GBV) is pervasive at South African higher education institutions (HEIs). Based on a media statement (dated 6 October 2016) by the Department of Higher Education and Training, GBV programmes at HEIs need to be evidence-informed, responsive, contextually relevant, inclusive and person-centred. The present article aims to explore the nature of GBV programmes currently implemented at HEIs in South Africa. A rapid review of the literature, supported by qualitative interviews with representatives of South African HEIs with medical campuses, was conducted. Findings indicate that there is an urgent need to clearly define GBV and to mention it explicitly in policy documents. In addition, research evidence on the effectiveness of prevention and response interventions at HEIs in South Africa is lacking. Challenges highlighted by the HEIs that were surveyed include the lack of trust by staff and students in the response and action plans of the response/task teams at HEIs, uncertainty with regards to the roles of relevant stakeholders and sectors when reporting incidents, as well as insufficient information about what GBV is. This study is intended to provide a baseline for further research evaluating current GBV programmes on medical campuses at HEIs, and highlights the need for an evidence-informed framework of the key ingredients for effective GBV response and prevention programmes.